2010
DOI: 10.1095/biolreprod.109.079863
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Estrogen Regulation of Hypothalamic KISS1 Gene in the Pig1

Abstract: Kisspeptin-GPR54 signaling plays an essential role in normal reproduction in mammals via stimulation of gonadotropin secretion. Here, we cloned the porcine KISS1 cDNA from the hypothalamic tissue and investigated the effect of estrogen on the distribution and numbers of KISS1 mRNA-expressing cells in the porcine hypothalamus. The full length of the cDNA was 857 bp encoding the kisspeptin of 54 amino acids, with the C-terminal active motif designated kisspeptin-10 being identical to that of mouse, rat, cattle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
100
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 31 publications
7
100
0
1
Order By: Relevance
“…sKp-29 showed a potent stimulatory effect on presumed ovulation, but sKp-40 had no effect on ovulation, indicating that sKp-29 is an endogenous kisspeptin in the musk shrew. Interestingly, suncus kisspeptin is much shorter than reported in other mammals, in which kisspeptin consists of 52-54 amino acids (9,17,24). Indeed, exogenous administration of sKp-29 mimicked the mating stimulus to induce presumed ovulation, and the sKp-29-induced ovulation was blocked completely by pretreatment with a GnRH antagonist.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…sKp-29 showed a potent stimulatory effect on presumed ovulation, but sKp-40 had no effect on ovulation, indicating that sKp-29 is an endogenous kisspeptin in the musk shrew. Interestingly, suncus kisspeptin is much shorter than reported in other mammals, in which kisspeptin consists of 52-54 amino acids (9,17,24). Indeed, exogenous administration of sKp-29 mimicked the mating stimulus to induce presumed ovulation, and the sKp-29-induced ovulation was blocked completely by pretreatment with a GnRH antagonist.…”
Section: Discussionmentioning
confidence: 88%
“…Accumulating evidence suggests that in many mammalian species the kisspeptin-GPR54 system plays a critical role in inducing gonadotropin secretion through stimulation of GnRH release (11)(12)(13)(14)(15)(16)(17). Kisspeptin neurons play a role in the generation of the surge mode of GnRH/LH release to mediate the estrogenpositive feedback effect and then ovulation (18)(19)(20)(21) as well as the pulsatile GnRH/LH release responsible for follicular maturation (22,23).…”
mentioning
confidence: 99%
“…The two SNP loci were in Hardy-Weinberg disequilibrium in the SN and GZ breeds (P < 0.05), which showed that the genotypic frequencies had been affected by selection, mutation or migration. So far, there have been some studies of the KISS1 gene as a candidate gene for reproductive traits in animals, which revealed that the KISS1 gene plays an important role in animal reproduction (Tomikawa et al, 2010). Huijbregts et al (2012) detected three SNPs (c.638insT, c.641C>G and c.645G>CA) in the 3ꞌ-UTR of the human KISS1 gene, and found that the c.645G>CA mutation was associated with central precocious puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, subsequent studies have shown that kisspeptin stimulates GnRH secretion via GPR54 on GnRH neurons [48][49][50]. The amino acid sequence of kisspeptin, especially the C-terminal 10-amino acid sequence, is well conserved in most mammals [51][52][53][54][55][56][57]. Hypothalamic kisspeptin neurons are mainly located in the anterior and posterior nuclei; i.e., the anteroventral periventricular nucleus (AVPV)/preoptic area (POA) and arcuate nucleus (ARC) [55,56,[58][59][60][61][62][63][64].…”
Section: Physiological Roles Of Kisspeptin and Gnih/rfrp-3mentioning
confidence: 99%
“…The amino acid sequence of kisspeptin, especially the C-terminal 10-amino acid sequence, is well conserved in most mammals [51][52][53][54][55][56][57]. Hypothalamic kisspeptin neurons are mainly located in the anterior and posterior nuclei; i.e., the anteroventral periventricular nucleus (AVPV)/preoptic area (POA) and arcuate nucleus (ARC) [55,56,[58][59][60][61][62][63][64]. Kiss1 mRNA expression in the AVPV/POA is increased in the afternoon during proestrus and is also upregulated by the administration of estrogen, whereas Kiss1 mRNA expression in the ARC is decreased by the administration of estrogen [61,63,[65][66][67].…”
Section: Physiological Roles Of Kisspeptin and Gnih/rfrp-3mentioning
confidence: 99%